Ecologia e biologia do camarão de água doce Macrobrachium amazonicum (Heller, 1862)(Decapoda: Caridea: Palaemonidae), em Minas Gerais - Bonatto, Carolina de Rezende (2015)
In the freshwater environment, the shrimp species Macrobrachium amazonicum is an important component in the energy flow and contributes largely for the nutrient cycling. Furthermore, this species has a large geographical distribution in Brazil and presents a broad intraspecific variability. In this way, the aim of this study is to evaluate the influence of the abiotic factors on the population structure and reproduction, and also elucidate issues about the dynamics and growth of the population. The samplings were performed monthly, from August 2013 to July 2014, at the Porto dam, on the municipality of Perdões, Minas Gerais. The animals were captured in an active way with 15 moves using a sieve net under the bank of aquatic macrophytes and taken to the laboratory to be sexed, measured the cephalothorax, count the eggs of the ovigerous females and determine the volume of the eggs. To evaluate the relative contribution of the abiotic factors: dissolved oxygen, rainfall, pH, temperature and conductivity, over the ecological and biological aspects of the specimens, it was used the hierarchical partitioning analysis. The cephalothorax lengths were distributed in size classes and demographic categories, and the growth curve was calculated according to the von Bertalanffy’s growth model. Among the five factors tested, only the dissolved oxygen did not present relation with other aspects. The conductivity affected negatively the abundance and the size classes 2 and 3, and positively the fecundity. However, the temperature had a positive relationship with the cephalothorax length, the number and volume of the eggs and also on the percentage of ovigerous females. A total of 2.502 shrimps were collected, being 1.248 males, 1.253 females, and only males translucent morphotypes. The abundance differed between seasons. The proportion between females and males in general did not differ from the expected 1:1, but the males were significantly bigger than females. The smaller specimen was 1.44 mm of cephalothorax, while the bigger specimen was 10.72 mm. About the expected growth, the maximum length of this population is 8.80 mm and the growth rate is 0.017 mm/month. The population of M. amazonicum in Minas Gerais appears to be well adapted to the region. The aspects observed regarding growth, reproduction and population structure confirm what is known for the crustaceans, of the Macrobrachium genus and for this species. Moreover, the results reinforce the importance of the abiotic factors on biology and ecology of the freshwater shrimps.